Micrometeorological and atmospheric diffusion studies At nuclear power station sites in India Part I : Wind profile studies (MAUSAM, 1970)
Micrometeorological and atmospheric diffusion studies were made at Tarapur and Rajasthan, two or the nuclear power station sites in India, in connection with the environmental safety programme. This paper describes the wind profile experiments and the analysis of wind data collected. The results are compared with similar analyses carried out on the published data from various other sites such as O'Neil (Nebraska. USA). Round Hill (Massachusetts, USA), Argonne (USA) and Kerang (Australia). Using the shear function defined as (1-S.){S8 where S is the non-dimensional wind shear (kZ/U*) (dU/dZ), it is shown that the analysis is critically dependent upon the value of roughness parameter Zo. A plot of the shear function versus Z/L' does not pass through the origin as required unless the proper value of Zo is chosen. This, in fact, can be considered as a test for the accuracy of Zo. It has also been observed that the shear function tends to a constant value when plotted against Z/L' in the stable regime indicating that KH/KM steadily decreases with Increase in stability.